The Strata/Machinic Assemblage and Architecture. - Abrahams, Gareth (Deleuze & Guattari Studies, 2020)
Much of the literature exploring the intersection between Deleuzo-Guattarian philosophy and architecture have focused on abstract theory, experimental projects and practices at the margins of the profession. But, one may ask, what of the mainstream, commercial practices that produce the offices, housing, shops, schools and community buildings that we see and engage with in our day-to-day lives? What of the everyday design decisions made by professional architects and technicians sitting at their desks and drawing boards? Are these to be excluded from architecture's engagement with Deleuzo-Guattarian philosophy? As I will show in this paper, Deleuze and Guattari's proposals for the strata and the machinic assemblage are drawn from their underlying attempt to expand Hjelmslev's planar composition from a tool used to analyse language to a conceptual framework used to analyse the formation and evolution of all things. There is nothing within the conceptual framework of the strata/machinic assemblage to suggest, therefore, that they should not be used to analyse such practices. With this in mind, this article considers how these concepts can be translated through and help provide new insight into a real-world design sequence taken from mainstream, commercial architectural practice. In doing so it will show how such practices can offer Deleuzo-Guattarian scholars a more nuanced insight into this conceptual framework and the concepts that form it.